Effect of haloperidol on transient outward potassium current in rat ventricular myocytes - Bébarová, Markéta; Matejovic, Peter; Pásek, Michal; Nováková, Marie (European journal of pharmacology, 2006)
Although sigma ligand haloperidol is known to affect repolarization in heart, its effect on potassium currents in cardiomyocytes has not yet been studied. We analyzed the effect of 1 micromol/l haloperidol on transient outward K(+) current (I(to)) in enzymatically isolated rat right ventricular cardiomyocytes using the whole-cell patch-clamp technique at room temperature. Haloperidol induced a decrease of amplitude and an acceleration of apparent inactivation of I(to), both in a voltage-independent manner. The averaged inhibition of I(to), evaluated as a change of its time integral, was 23.0+/-3.2% at stimulation frequency of 0.1 Hz. As a consequence of slow recovery of I(to) from the haloperidol-induced block (time constant 1482+/-783 ms), a cumulation of the block up to about 40% appeared at 3.3 Hz. We conclude that haloperidol causes a voltage-independent block of I(to) that cumulates at higher stimulation frequencies. Based on the computer reconstruction of experimental data, a block of I(to)-channels in both open and open-inactivated states appears to be likely mechanism of haloperidol-induced inhibition of I(to).
Keywords: draslíkové kanály; Animals; Receptors, sigma; Heart Ventricles; Models, Statistical; antipsychotika; membránové potenciály; Antipsychotic Agents; Rats, Wistar; Myocytes, Cardiac; Electrophysiology; srdeční komory; haloperidol; receptory sigma; statistické modely; Membrane Potentials; Haloperidol; Male; kardiomyocyty; Patch-Clamp Techniques; krysa rodu Rattus; elektrofyziologie; Potassium Channels; zvířata; mužské pohlaví; metoda terčíkového zámku; Rats; potkani Wistar